Internal structure and measurement invariance of the Children’s Hassles Scale in adolescents - Navarro-Loli, Jhonatan S. (2020)
Background: Daily stressors are events of low emotional impact but with high probability of occurrence, which in adolescence can come from school, friends and family. Therefore, it is necessary to have instruments for their evaluation. Aim: To determine the validity of the internal structure and measurement invariance of the Children’s Hassles Scale in adolescents from Lima, Peru. Method: The sample consisted of 524 adolescents between 14 and 18 years old. The internal structure was evaluated by confirmatory factor analysis, and the measurement invariance was assessed using a procedure in which restrictions were added progressively. Finally, reliability was obtained through coefficient omega. Results: The original factor structure is not replicated in the Peruvian sample. On the contrary, a parsimonious structure of two oblique factors oriented to stressors in school and family presents robust indicators and measurement invariance among males and females. Conclusion: The instrument can be used for research purposes in the Peruvian setting, which lacks instruments for measuring daily stressors in adolescents. Authorship contribution JNL: Conception and study design, writing of the initial version of the article, data analysis and final revision of the article. AAL: Introduction and final revision of the article.